(untitled) - Souza-Santos, Marcio L. de (New York, 2004)
Correlating theory and application, Solid Fuels Combustion and Gasification demonstrates the operational mechanisms, modeling, and simulation of equipment for the combustion and gasification of solid fuels. This reference illustrates how to optimize the design of future units and the operation of existing systems with recommendations and guidelines from a seasoned professional in the field. It shows how chemical and physical transformations, equipment design and operational conditions, and transport phenomena interact for correct simulation and forecasting of system operations, and displays methods to build computer simulation programs to predict equipment performance
Keywords: Fuel combustion,Fuel combustion,Coal gasification; Combustion,Equipment and supplies,Combustion